PENGARUH DOSIS RHIZOCTONIA Binukleat (BNR) dan PUPUK POSFOR TERHADAP PERTUMBUHAN BENIH VANILI (Vanilla planifolia Andrew) - -, Haryuni; Soemarah K.D, Tyas; Nuryati, Titik (Universitas Muhammadiyah Semarang, 2015)
The aims of this research are to study the effec of Rhizoctonia binucleat (BNR) and dosage of phosfor to growth vanilla seedling (Vanilla planifolia Andrew). The research conducted at the Faculty of Agriculture, Tunas Pembangunan University of Surakarta Central of Java Province. The experiment was arranged in a completely randomized factorial design, consisted of two factors. The first factor was BNR inoculation and non inoculation of vanilla seedling (M0, M1, M2, M3) that consisted of (0,5, 10, 15) g/polibag the second factor was phosphor fertilizer (P1, P2, P3) that consisted of (3, 6, 9) g/polibag. The research by using Analysis Variance (ANOVA), if there are differences among treatment continued with Duncan Multiple Range Test (DMRT) at 5 % level. The showed that the research was increase growth (length of bud, number of leaves, gird of stem, fresh weight, dry weight, fresh of root.. The highest result to all parameters of growth was the inoculated BNR 15 g/polibag (M3) and the dosage phosphor fertilizer 9 g/polibag (P3).Key words: Rhizoctonia binukleat (BNR), phosfor, vanilla, growth